Next-Day Effects of Ramelteon (8 mg), Zopiclone (7.5 mg), and Placebo on Highway Driving Performance, Memory Functioning, Psychomotor Performance, and Mood in Healthy Adult Subjects - Mets, Monique A.J.; de Vries, Juna M.; de Senerpont Domis, Lieke M.; Volkerts, Edmund R.; Olivier, Berend; Verster, Joris C. (Sleep (New York, N.Y.), 2011)
To evaluate the next-morning residual effects of ramelteon (8 mg), zopiclone (7.5 mg), and placebo on driving performance, memory functioning, psychomotor performance, and mood in healthy adult subjects following bedtime dosing and a middle of the night awakening. Single-center, randomized, double-blind, double-dummy, placebo-controlled, crossover study. Utrecht University, The Netherlands. 30 healthy volunteers (15 males and 15 females). a single dose of ramelteon (8 mg), zopiclone (7.5 mg), and placebo, administered at bedtime. A balance test was performed at night. Other tests were performed the following morning, 8.5 h after administration. Subjects performed a 100-km highway driving test in normal traffic. Primary outcome measure was the standard deviation of the lateral position (SDLP), i.e., the weaving of the car. After driving, cognitive, memory, and psychomotor tests were performed and mood was assessed. SDLP was significantly increased after the intake of ramelteon (+2.2 cm) and zopiclone (+2.9 cm). Ramelteon and zopiclone produced significant impairment on reaction time (P<0.024) in the Sternberg Memory Scanning Test, slow (P<0.007) and fast (P<0.010) tracking, reaction speed (P<0.015) and tracking (P<0.001) in the Divided Attention Test, and delayed recall (P<0.032) in the Word Learning Test. In contrast to ramelteon, zopiclone additionally impaired performance on the Digit Symbol Substitution Test (P<0.001) and the balance test (P<0.001). Ramelteon (8 mg) and zopiclone (7.5 mg) significantly impaired driving performance, cognitive, memory, and psychomotor performance the morning following bedtime administration. In contrast to zopiclone, ramelteon produced no balance impairments. CLINICAL TRIAL IDENTIFIER: NCT00319215 (www.clinicaltrials.gov).